دلالة الصورة الفنية في قصة موسى - عليه السلام - في القرآن الكريم. سورة الشعراء نموذجًا: The Significance of The Artistic Image in The Story of Moses - Peace Be Upon Him - In The Holy Quran. Sura Poets Model - Arshad, Mohamad Syauqi; Mohammed Al-Baz Al-Sheikh, Mohammed Radhi; Zabedin, Mohammed Azizul Rahman (SIBAWAYH Arabic Language and Education, 2020)
Every Muslims, regardless of his ability to recite the Quran or mastering the Arabic language, receive a great reward from Allah for reciting the Quran, contemplating its meaning and applying its teaching. But it is noticeable that some readers of Quran while depending on Quranic translation fail to comprehend its interpretation perfectly. Therefore, this research studies the concept of the technical image and its vocabulary in Quran and its artistic and semantic effect. In addition, it also aims to highlight its role in persuasion and influence of the readers. This research comes to detail the mysterious translation of some translation readers, by drawing of photographing a frame, situation, atmosphere, surrounding conditions, environment, or state of an accident, as if we could imagine it in front of us. This research aims to study the artistic image in the story of Moses – peace be upon him – and what is related to it, and clarify its role in enriching the Quranic significance, clarify the will of God Almighty, and communicate his message to humanity. Other than that, this study also explains the role of visual art in enriching the Quran connotations, explaining what Allah really meant (through His word), and communicating His message to mankind. This study focuses on the artistic portrayal of the story of Moses in the Surah al-Shu’araa’, and examines its artistic, semantic and its source, concept and impact.